Pembuatan dan Karakterisasi Bolus Berbahan Silicone Rubber RTV 00A dengan Variasi Komposisi Clear Catalyst - Fajriani, Dewi; Muttaqin H.S, Afdhal; Ilyas, Muhammad (Universitas Andalas, 2024)
The manufacture and characterization of boluses made from Silicone Rubber RTV 00A with 4% clear catalyst composition have been carried out. The bolus was made with a size of (15x15) cm and the thickness of 1.0 cm. Each bolus sample was characterized to obtain physical properties (density and water absorption capacity), mechanical properties (tensile strength, strain, and elastic modulus), Relative Electron Density (RED), Percentage Surface Dose (PSD), and absorbed dose. RED value were obtained through tomographic images using a CT-Simulator by determining 5 Region of Interest (ROI) points. PSD and absorbed dose values were measured using a plan parallel chamber detector with energy of 9 MeV. The bolus has a density of (0.815 ± 0.150) g/cm³ and water absorption of (12.42 ± 0.01)%, tensile strength of (0.286 ± 0.091) MPa, an elongation of (22.93 ± 0.22)%, and an elastic modulus of (5.880 ± 11.52) MPa. The RED value of (1.114 ± 0.021) g/cm³ a PSD of 132.40% and an absorbed dose of 233.82 cGy in energy of 9 MeV. RTV 00A can be developed as a bolus base material.